THE ANALYSIS OF LECTURERS’ ROLE IN FORMING CLASSROOM INTERACTION AMONG STUDENTS: A CASE STUDY AT SMARATUNGGA BUDDHIST STUDY COLLEGE - Budiyanto Budiyanto (Program Studi Pendidikan Bahasa Inggris Institut Pendidikan dan Bahasa Invada, 2023)
The importance of classroom interaction in EFL (English as a Foreign Language) instruction is occasionally lost on educators. The interaction in the classroom is crucial to assimilating and embracing the target language. As a result of successful information transfer from the teacher to the students, good contact can lead to an increase in students' language acquisition. Because the focus of the classroom interaction study is on how interlocutors make meaning of one another's contributions, the findings can be used as a diagnostic tool to identify issues with discourse management and crucial occurrences that learners confront. Researchers used qualitative methods, including discourse analysis and case studies. Smaratungga Buddhist College Study College was conducted this investigation. The researchers anticipate that learners will be motivated and inspired by the interactional situation. This study focuses on how the teacher creates interaction in the classroom. The success of all outcomes depends on how well students interact. Researchers agree with their actions while they are interacting with the teacher or one another.